Niektóre właściwości chemiczne i fizyko-chemiczne osadów poflotacyjnych ze zbiornika "Konrad" nr 3 w Iwinach = Some chemical and physic properities of the flotation sediments from the reservoir "Konrad" no. 3 in Iwiny village - Szerszeń, Leszek; Chodak, Tadeusz; Gawron, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In article presents some physical properties (bulk density, volume density and total porosity) and physic-chemical properties of postflotation sediments of the "Konrad" nr 3 reservoir in Iwiny. Affirm diversity analysed physical and physic-chemical properties of postflotation sediments.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)